Calculation path to create clutching efforts in electrical complexes to reduce residual stress - Kondratenko, I.; Schylcov, A.; Vasyuk, B. (Energy and Automation, 2015)
The parameters of the electric circuit to generate a given time and efforts clutching his actions in the electrical sector to reduce residual stresses.